GOVERNANCE: STATIC, DYNAMIC, AND CHAOTIC - Riant Nugroho; Agustina Setiawan (Universitas Jenderal Ahmad Yani, 2025)
Governance is the key success of Government. The reforming governance among developing countries is difficult, costly, and exhausted. It was caused by the less-comprehensive of the understanding of governance itself. There are three types or mode of governance, historically: static, dynamic, and chaotic. The static is governance concept which was develop in 1980s and still as mainstream until today practices among Government, includes in Indonesia. The finding of the second types of dynamic governance has been introduced, but in fact it was facing some new challenges from character of the people to the policy. Some countries with factor of a fit culture for dynamic governance are effectively able to develop the capabilities to exercise governance. Some other countries do not have, or they have but insufficient. Chaotic governance is the new imperative for today and tomorrow government. It is governance in the digital age. Scholars and leaders of Governments need to have a same premise and commitment to use the recent technology of digital profoundly.